Effect of promoter strength and signal sequence on the periplasmic expression of human interferon-α2b in Escherichia coli - Ramanan, Ramakrishnan Nagasundara (Academic Journals, 2010)
Two plasmids, pFLAG-ATS and pET 26b(+), were studied for the periplasmic expression of recombinant human interferon-α2b (IFN-α2b) in Escherichia coli. The pFLAG-ATS contains ompA signal sequence and tac promoter while pET 26b(+) contains pelB signal sequence and T7lac promoter. It was observed that periplasmic expression of IFN-α2b from pET 26b(+) was around 3000 times higher than pFLAG-ATS. Difference in the expression level was attributed to the difference in the promoters and the signal sequences. In silico analysis of mRNA secondary structures were analyzed using Vienna RNA package and MFOLD. The resultssuggested that the increase of expression would mainly due to the difference in the translation initiation associated with secondary structure of mRNA transcribed by both plasmids.